RANCANG BANGUN SISTEM INFORMASI ABSENSI SISWA BERBASIS WEB MENGGUNAKAN QR CODE DENGAN FITUR LAPORAN OTOMATIS PADA SDN CIPAYUNG 01 - Jaswa Ariansya; Titania Aulia Azahra (Jurnal Riset Sistem Informasi, 2026)
The development of information technology has significantly influenced various fields, including education. SDN Cipayung 01 still uses a manual student attendance system that relies on attendance books, requiring considerable time and risking recording errors. Based on these problems, a web-based student attendance information system using QR Code with automatic report features was developed. The system was built using the PHP programming language and MySQL database, accessible through a web browser. Students simply scan their QR Code to record attendance, which is then automatically saved to the database. Testing results show that the QR Code-based attendance system reduces attendance time from 10-15 minutes to 2-5 minutes per class, achieving approximately 66% time efficiency. All system features performed successfully in functional testing, including login, QR scanning, student data management, daily recaps, monthly reports, and CSV export.